2020
DOI: 10.21037/apm-19-649
|View full text |Cite
|
Sign up to set email alerts
|

Association of systolic blood pressure with atrial fibrillation among treated hypertensive patients

Abstract: Background: Although many studies have suggested the association between elevated blood pressure and atrial fibrillation (AF), how the relationship between systolic blood pressure (SBP) and AF differ by antihypertensive treatment has been unclear. Therefore, this study aimed to explore the relationship between SBP and AF in hypertensive patients with or without antihypertensive treatment.Methods: This was a cross-sectional study that enrolled 7,808 hypertensive patients aged ≥18 years old in 2013 in Guangdong,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Atrial Fibrillation (AF). Atrial fibrillation (AF) is the most common arrhythmia in clinics, and its risk increases with age [119]. Both human and animal data confirm the role of oxidative stress in the pathogenesis of AF [120,121].…”
Section: Myocardial Infarction (Mi)mentioning
confidence: 97%
See 1 more Smart Citation
“…Atrial Fibrillation (AF). Atrial fibrillation (AF) is the most common arrhythmia in clinics, and its risk increases with age [119]. Both human and animal data confirm the role of oxidative stress in the pathogenesis of AF [120,121].…”
Section: Myocardial Infarction (Mi)mentioning
confidence: 97%
“…E2F1/miR-30b/Cyclophilin D forms a pathway in regulating hydrogen peroxideinduced necrotic cell death [116]. During hydrogen peroxide induced apoptosis, Wang et al found that both E2F1/miR-421/Pink signal pathway and miR-361/PHB1 function in regulating mitochondria fission and apoptosis [118,119]. All these results indicate that functional noncoding RNAs also play important role in a series of hydrogen peroxideinduced cellular responses.…”
Section: Myocardial Infarction (Mi)mentioning
confidence: 99%
“… 30 In subjects receiving antihypertensive treatment, a J-shaped relationship between SBP and AF was observed. 31 , 32 In the present study, SBP in the range 100–120 mmHg was more likely to complicate AF than SBP above that range, and there was no J-shaped relationship between SBP and AF. We present 3 hypotheses regarding the negative correlation between SBP and AF: (1) low SBP may, indeed, increase the risk of AF via chronic coronary ischemia, myocardial proliferation, and fibrosis induced by inadequate coronary perfusion; (2) low SBP may be the result of AF or AF-related cardiac structural and functional abnormalities; and (3) subjects with higher SBP are more likely to receive better clinical care and more antihypertensive medications, which play an important role in the mutually affected relationship between hypertension and AF.…”
Section: Discussionmentioning
confidence: 39%
“…30 In subjects receiving antihypertensive treatment, a J-shaped relationship between SBP and AF was observed. 31,32 In the present study, SBP in the range 100-120 mmHg was more likely to complicate AF than SBP above that range, and there was no J-shaped relationship between SBP and AF. We present 3 hypotheses regarding the negative correlation between SBP and AF:…”
Section: Interpretation Of Featuresmentioning
confidence: 42%
“…Studies show that exposure to higher systolic blood pressure increases the risk of AF by 19% (advantage ratio of 1.19 [1.12 to 1.27] per 10 mmHg) [25]. Several studies have shown that effective blood pressure control is beneficial in reducing the incidence of AF/AFL [26][27][28]. In terms of the development of the attributable impact of high BMI, its contribution to the disease burden of AF/AFL is on the rise.…”
Section: Discussionmentioning
confidence: 99%